David against Goliath? The rise of coastal states at the Indian Ocean Tuna commission - Sinan, Hussain; Andriamahefazafy, Mialy; Robertson, Kerrie (Frontiers in Marine Science, 2022)
Tuna regional fisheries management organizations (RFMOs) have long suffered from the domination of distant water fishing nations (DWFNs) in decision-making processes. The Indian Ocean Tuna Commission (IOTC) is no exception. In recent years, coastal states of the Indian Ocean (IO) have tried to change this dynamic - led by countries like the Maldives, Kenya, South Africa, and Australia - to deliver greater benefits to the region including East Africa. These countries are gathered under the informal group of G16 and have increasingly improved their involvement at the IOTC. Here, we ask, how has the rise of the G16 benefited coastal States in the IO region and what are the challenges going forward. To do this, we analyzed proposals submitted by the G16 for conservation and management measures and the participant list of the Commission meetings in the past 10 years. Unveiling the efforts of coastal countries is essential to guide further capacity building needed in the region in terms of negotiations. We also call for international oversight towards the actions of DWFNs, such as the EU, whose actions often differ markedly from their claims of being sustainability champions. The G16’s work is essential to keeping coastal States of the Indian Ocean in the driver’s seat for managing Indian Ocean fisheries to the benefit of future generations.